2013
DOI: 10.1038/sc.2013.106
|View full text |Cite
|
Sign up to set email alerts
|

Local non-viral gene delivery of apoptin delays the onset of paresis in an experimental model of intramedullary spinal cord tumor

Abstract: Objective: The objective of this study is to evaluate the safety and efficacy of a tumor-specific apoptosis-inducing gene, apoptin, as delivered by the non-viral carrier, PAM-RG4, in an animal model of spinal cord tumor. Methods: Male Sprague-Dawley rats were given a 2.5-ml intramedullary injection of C6 glioma (100 000) cells and randomized into three groups (day 0). On day 5, animals received a 7.5-ml intramedullary injection of Dulbecco's modified Eagle's medium (Group 1; n ¼ 7), PAM-RG4/control gene polypl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In conclusion and based upon comparison between all AXM for IMSCT, we are convinced that intramedullary transplantation of tumor cells into the spinal cord of immunocompromised rats is currently the most established and most suitable disease model. Numerous studies have demonstrated that surgical intervention on the spinal cord of rats is safe and feasible [16][17][18][19][20][21][22][23][24][25][26][27]. Furthermore, housing of these organisms is easy and cost effective [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion and based upon comparison between all AXM for IMSCT, we are convinced that intramedullary transplantation of tumor cells into the spinal cord of immunocompromised rats is currently the most established and most suitable disease model. Numerous studies have demonstrated that surgical intervention on the spinal cord of rats is safe and feasible [16][17][18][19][20][21][22][23][24][25][26][27]. Furthermore, housing of these organisms is easy and cost effective [28].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approach to the spinal cord was always performed using a laminectomy of one or two spinal column segments. In most cases, tumor cells and not tumor tissue were injected in the mid-thoracic spinal cord, which routinely led to hind limb paresis and finally to paraplegia [15,16,19,20,[22][23][24][25][26][27][30][31][32][33]. Although cervical spinal cord might be more suitable for tumor cell transplantation regarding the increased volume of central nervous tissue, this approach was less frequently performed and routinely caused autonomic dysfunction [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A similar starburst cationic polymer, L-arginine-grafted polyamidoamine (PAM-RG4), has been used to successfully deliver vectors encoding genes that induce tumor cell apoptosis to spinal cord tumor. 167 …”
Section: Technologies For Delivery Of Gene Therapies To the Spinal Comentioning
confidence: 99%
“…Furthermore, this combination resulted in strong natural killer activity and LLC tumor-specific CTL responses with high levels of the Th1 cytokine IL-2 and IFN-c [204]. Apoptin is also effective against brain and spinal cord tumors [205,206]. Polyamidoamine dendrimer with an arginine surface (PAM-RG4) mediated transfer of plasmid encoding apoptin (PAM-RG4/apoptin gene polyplex) effectively inhibited tumor growth in U87MG cells induced tumor in nude mice [205] and C6 cells induced tumor growth in the spinal cord of Sprague-Dawley rats [206].…”
Section: Apoptinmentioning
confidence: 99%